2014
DOI: 10.1016/j.brainres.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Trans-sodium crocetinate improves outcomes in rodent models of occlusive and hemorrhagic stroke

Abstract: Trans-sodium crocetinate (TSC) is a novel carotenoid compound capable of enhancing the diffusion of small molecules in aqueous solutions. TSC improves the diffusion of oxygen and glucose, and increases oxygenation in ischemic brain tissue. TSC also dampens the intensity of an ischemic challenge during an ongoing ischemic event. The current study examined the impact of TSC in rat models of ischemic and hemorrhagic stroke. Rat three vessel occlusion (3VO), and combined 3VO and one vessel occlusion (3VO/1VO) mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Previous evidence has shown that hematoma size is not significantly affected by TSC treatment [11]. The locations of the sampling areas in the vicinity of the hematoma are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous evidence has shown that hematoma size is not significantly affected by TSC treatment [11]. The locations of the sampling areas in the vicinity of the hematoma are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for that study was TSC might reasonably be used for treating ischemic stroke prior to differential diagnosis of the type of stroke underway, if it does not to aggravate outcomes under conditions of hemorrhagic stroke. Although TSC did not significantly affect hematoma volume, it actually improved certain outcomes after experimental ICH, including edema and a hemorrhagic volume [11]. Finally, TSC has successfully completed two phase I safety trials and a phase I/IIa trial for peripheral artery disease, indicating that this compound can be administered safely in humans [18,19].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations